# Solve $\left ( 1- \sqrt{2}\sin x \right )\left ( \cos 2x+ \sin 2x \right )= \frac{1}{2}$ [closed]

Solve $$\left ( 1- \sqrt{2}\sin x \right )\left ( \cos 2x+ \sin 2x \right )= \frac{1}{2}$$ Now I did not understand how can i solve that.

I have tried substituting $\cos(2x)=\cos^2(x)−\sin^2(x)$ and$\,$ $\sin(2x)=2\sin(x)\cos(x)$,

the equation is now $(1−\sqrt2\sin(x))(\cos^2(x)−\sin^2(x)+2\sin(x)\cos(x))=\frac12$

Help Required

Thanks

## closed as off-topic by Henrik, Rohan Shinde, Namaste, Saad, Xander HendersonMar 26 '18 at 0:34

This question appears to be off-topic. The users who voted to close gave this specific reason:

• "This question is missing context or other details: Please improve the question by providing additional context, which ideally includes your thoughts on the problem and any attempts you have made to solve it. This information helps others identify where you have difficulties and helps them write answers appropriate to your experience level." – Henrik, Rohan Shinde, Namaste, Saad, Xander Henderson
If this question can be reworded to fit the rules in the help center, please edit the question.

• @TrầnThúcMinhTrí Not anyone is an expert in English. The OP truly hasn't posed an attempt on a solution but judging his English knowledge isn't correct. – Rebellos Mar 25 '18 at 12:00
• No, I mean I just don't like how somebody ask a question that says something too short like "Help needed"; "Help required", etc. There is a page that mentions about writing good questions. – user061703 Mar 25 '18 at 12:02
• I have tried $\cos 2x= \cos ^{2}x- \sin ^{2}x$ and $\sin 2x= 2\sin x\cos x$, the equation is $\left ( 1- \sqrt{2}\sin x \right )\left ( \cos^{2}x- \sin ^{2}x+ 2\sin x\cos x \right )= \frac{1}{2}$ – user530708 Mar 25 '18 at 12:04
• Can you edit my queston? – user530708 Mar 25 '18 at 12:05
• Perhaps the $t=tan(x)$ substitution would work? – Sorfosh Mar 25 '18 at 16:17

Multiplying by $1+\sqrt 2 \sin x$ on both sides and using $1-2 \sin^2 x = \cos 2x$ we get

$\cos 2x (\cos 2x + \sin 2x ) = \dfrac{1+\sqrt 2 \sin x}{2}$

or $1+\cos 4x + \sin 4x = 1+\sqrt 2 \sin x$

or $\dfrac{\sin 4 x + \cos 4x}{\sqrt 2} = \sin x$

or $\sin \left(4x+\dfrac{\pi}{4} \right) = \sin x$ which can be easily solved

• From there, $\arcsin$ both sides, right? – ericw31415 Mar 25 '18 at 20:53
• I tried to use Wolfram alpha but your answer were not true. The equation has 5 roots like John Glenn. Thanks for your idea very much! – user530708 Mar 26 '18 at 0:27

You can substitute: $$y=2x\Rightarrow x=\frac y2$$ $$\left ( 1- \sqrt{2}\sin \frac y2 \right )\left ( \cos y+ \sin y \right )= \frac{1}{2}$$ Remember that: $$\sin\frac\theta2=\pm\sqrt{\frac{1-\cos\theta}2}$$ So you get: $\left ( 1- \sqrt{2} (\pm\sqrt{\frac{1-\cos\theta}2})\right )\left ( \cos y+ \sin y \right )= \frac{1}{2}$, which simplifies to: $$\left ( 1 \pm\sqrt{{1-\cos\theta}}\right )\left ( \cos y+ \sin y \right )= \frac{1}{2}$$ Solving for the first case:$\left ( 1 -\sqrt{{1-\cos\theta}}\right )\left ( \cos y+ \sin y \right )= \frac{1}{2}$ \begin{align} \cos y-(\cos y) \sqrt{1-\cos (y)}+\sin y-(\sin y) \sqrt{1-\cos (y)}&=\frac{1}{2}\\ -(\cos y) \sqrt{1-\cos (y)}-(\sin y) \sqrt{1-\cos (y)}&=\frac{1}{2}-\cos y-\sin y\\ \left(-(\cos y) \sqrt{1-\cos (y)}-(\sin y) \sqrt{1-\cos (y)}\right)^2&=\left(\frac{1}{2}-\cos y-\sin y\right)^2\\ \end{align}

We then evaluate each side: \begin{align} \left(-(\cos y) \sqrt{1-\cos (y)}-(\sin y) \sqrt{1-\cos (y)}\right)^2&=\cos ^2 y-\cos ^3 y+2 (\cos y) (\sin y)-2 \left(\cos ^2 y\right) (\sin y)+\sin ^2 y-(\cos y) \left(\sin ^2 y\right)\\ \left(\frac{1}{2}-\cos y-\sin y\right)^2&=y \sin ^2-y \sin +y \cos ^2-y \cos +2 (y \sin ) (y \cos )+\frac{1}{4}\\ \end{align}

Continuing the computation, we get: \begin{align} -\frac{1}{4}+\cos y-\cos ^3 y+\sin y-2 \left(\cos ^2 y\right) (\sin y)-(\cos y) \left(\sin ^2 y\right)&=0\\ -1+4 (\cos y)-4 \left(\cos ^3 y\right)+4 (\sin y)-8 \left(\cos ^2 y\right) (\sin y)-4 (\cos y) \left(\sin ^2 y\right)&=0\\ -1-4 (\sin y)+8 \left(\sin ^3 y\right)&=0\\ (2 (\sin y)+1) \left(-1-2 (\sin y)+4 \left(\sin ^2 y\right)\right)&=0\\ \end{align} We get the correct answers as: $$y=\begin{cases} 2 \pi n+\frac{7 \pi }{6}\qquad{n \in \mathbb{Z}}\\ 2 \pi n+\frac{3 \pi }{10}\\ 2 \pi n+\frac{11 \pi }{10}\\ 2 \pi n+\frac{19 \pi }{10}\\ \end{cases}$$

And since $x=\frac y2$, then the first set of solutions for $x$ will be: $$x=\begin{cases} 2 \pi n+\frac{7 \pi }{12}\qquad{n \in \mathbb{Z}}\\ 2 \pi n+\frac{3 \pi }{20}\\ 2 \pi n+\frac{11 \pi }{20}\\ 2 \pi n+\frac{19 \pi }{20}\\ \end{cases}$$

The second case:$\left ( 1 +\sqrt{{1-\cos\theta}}\right )\left ( \cos y+ \sin y \right )= \frac{1}{2}$ returns the following answers: $$y=\begin{cases} 2 \pi n-\frac{ \pi }{6}\qquad{n \in \mathbb{Z}}\\ 2 \pi n+\frac{7 \pi }{10}\\ \end{cases}$$ However,the second answer for $x$ does not hold for the original equation. And thus, our final solution set contains: $$\therefore x=\begin{cases} 2 \pi n-\frac{ \pi }{12}\qquad{n \in \mathbb{Z}}\\ 2 \pi n+\frac{7 \pi }{12}\\ 2 \pi n+\frac{3 \pi }{20}\\ 2 \pi n+\frac{11 \pi }{20}\\ 2 \pi n+\frac{19 \pi }{20}\\ \end{cases}$$

• John Glenn, thanks! – user530708 Mar 26 '18 at 0:23